2019
DOI: 10.1016/j.wasman.2019.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of physical separation of metals from soils contaminated with municipal solid waste ashes and metallurgical residues

Abstract: Environmental legislation is forcing industrialized countries to rehabilitate contaminated lands. Expensive solutions are available to treat soils contaminated by metals (e.g., solidification, stabilization, and landfilling). Physical remediation techniques, which are less expensive, are able to efficiently separate metals from contaminated soils under specific physical conditions. In the current study, densimetric and mineralogical characterization of fractions of soil between 0.25 and 4 mm contaminated by mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Similar to the results of this study, these technogenic materials are enriched in metal (loid)s ( Table S8 – note the striking coincidence of metal (loid) concentrations in MSWI ashes deposited/buried in soils from different countries), while metal (loid) concentrations in the surrounding or overlying soil are usually lower and dependent on the distance from the ash deposits and the ash content of the soil [ 107 , 112 ]. Several authors characterised the mineralogical composition of old MSWI ashes and showed that quartz, calcite, magnetite, hematite and possibly albite were the dominant minerals [ 51 , 63 , [109] , [110] , [111] ], which is also a typical feature of the old MSWI ashes of this study. Limited leaching of metal (loid)s is characteristic of incineration ashes exposed to atmospheric conditions for a long time.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Similar to the results of this study, these technogenic materials are enriched in metal (loid)s ( Table S8 – note the striking coincidence of metal (loid) concentrations in MSWI ashes deposited/buried in soils from different countries), while metal (loid) concentrations in the surrounding or overlying soil are usually lower and dependent on the distance from the ash deposits and the ash content of the soil [ 107 , 112 ]. Several authors characterised the mineralogical composition of old MSWI ashes and showed that quartz, calcite, magnetite, hematite and possibly albite were the dominant minerals [ 51 , 63 , [109] , [110] , [111] ], which is also a typical feature of the old MSWI ashes of this study. Limited leaching of metal (loid)s is characteristic of incineration ashes exposed to atmospheric conditions for a long time.…”
Section: Resultssupporting
confidence: 53%
“…To the best of our knowledge, few studies have addressed metal (loid) concentrations in soils containing or in contact with waste incinerator ashes [ [107] , [108] , [109] , [110] , [111] , [112] ]. Similar to the results of this study, these technogenic materials are enriched in metal (loid)s ( Table S8 – note the striking coincidence of metal (loid) concentrations in MSWI ashes deposited/buried in soils from different countries), while metal (loid) concentrations in the surrounding or overlying soil are usually lower and dependent on the distance from the ash deposits and the ash content of the soil [ 107 , 112 ].…”
Section: Resultsmentioning
confidence: 99%